Microstructural evolution after heat treatment of high specific strength steel: Fe-13Al-16Mn-5Ni-0.8C and correlation with tensile properties - Kumar N.; Singh K.; Singh A. (My University, 2025)
The present work investigates the microstructure and tensile properties of lightweight steel (Fe-13Al-16Mn-5Ni-0.8C) annealed at two temperatures: 480 °C and 840 °C. A systematic study of the emergence of phases and precipitates using transmission electron microscopy (TEM), scanning electron microscope (SEM) and electron back-scattered diffraction (EBSD) has been carried out. The tensile properties of the samples annealed differently have been studied and correlated with the microstructure. After annealing at 480 °C, κ-carbides were observed inside the austenite grain along with the presence of DO3 adjoining austenite. However, after annealing at 840 °C ordered-particles with two different morphologies (fine spheres and rod-shaped) were formed inside the ferrite grains and needle-shaped particles were formed inside the austenite grains. The high-angle annular dark-field (HAADF) analysis suggested that the Fe-Mn type B2-particles were formed inside the ferrite grains whereas Ni-Al type B2-particles were formed inside the austenite grains. The samples annealed at 840 °C showed higher strength and ductility but the sample annealed at 480 °C showed high strain hardening. The fractography images showed a multi-featured surface carrying a signature of the multi-phase microstructure. © 2022 Acta Materialia Inc.